Experimental and Numerical Analysis of the Bolt Connections in a Low-Rise Precast Wall Panel Structure System - Wei Guo; Zhipeng Zhai; Zhiwu Yu; Feng Chen; Yongzhi Gong; Tao Tan (Advances in Civil Engineering)
This paper develops a novel dry connection utilizing high-strength bolts and introduces the corresponding low-rise precast wall panel structure system. To investigate the seismic performance of the structure system with full bolt connections, monotonic loading tests of the connection joint and cyclic lateral loading tests of three full-scaled precast shear walls are both conducted. Based on the test data, axial and shear mechanical models of the connection are given. Meanwhile, experimental results show that the failure mode of the connection is dominated by anchored rebar ductile rupture, and the precast structure system presents a stable energy dissipation capacity and a good seismic ductility. The numerical model of the precast shear wall is then developed and validated by the cyclic loading test. Also a simplified calculation method to predict the lateral strength of the precast shear wall is proposed. According to the calculation results, the distance between the center of the connection and the edge of the shear wall is suggested to be 150 mm, while the wall thickness is recommended to be 120 mm or 150 mm. Finally, a three-story precast wall panel structure is employed to assess the collapse performance of the proposed precast structure system by using the presented numerical model. The results indicate that the proposed structure system with full bolt connections has high stiffness and high seismic resistance against collapse.